Electrical load-sizing methodology to aid conceptual and preliminary design of large commercial aircraft - Seresinhe, Ravinka; Lawson, Craig P. (Sage, 2014)
The importance of the more electric aircraft has been highlighted in many publications, projects and industrial presentations. By definition, the more electric aircraft concept achieves the majority of the required system functionality by using electrically powered sub-systems and components. This manifests itself in much higher electrical power demands on-board aircraft, compared to conventional architectures. This presents many challenges in the design process. To alleviate the risk and choose the optimum architectures for the systems on the aircraft, it is essential to incorporate the characteristics and possible configurations of the electrical network in the conceptual and preliminary design stages. Hence the current practice of performing an electrical load analysis at the detailed design stage is not adequate. To address this gap, this paper presents a viable and robust methodology to define requirements, size components and systems and calculates the electric power requirements at the preliminary design stages. The methodology uses the conventional aircraft, systems and components as the baseline and uses mathematical techniques and logical sequences of component operation, developed through the research, to size electrical load profiles for conventional aircraft. It then adapts this result to the more electric aircraft concept by adding key components that would account for the difference between a conventional system and a more electric system. The methodology presented here makes the design process more robust and aids the choice of the optimum design for the aircraft.
Keywords: Aircraft design; aircraft systems; electrical load analysis; more electric aircraft